Experimental study of 70 Divergen Angle of Diffuser on Liquid Jet Gas Ejector - Daru Sugati; Eka Yawara (Retii, 2016)
Aim of  this research is founded  the effect  of  gas-liquid ratio on diffuser performance. Diffuser attached on  end of throat of ejectors. Ejector employed water as a motive fluid and air as the entrained fluid.  downward flow is direction of flow in the ejector . Ejector generated bubble flow from entrainment and mixing process in the throat section. Performance of diffuser was measured from pressure recovery value. Pressure recovery is differential pressure of upstream and down stream of diffuser divide by kinetic energy on the upstream diffuser.  The result of the experimental is increasing of void fraction up to value 0.2, its became pressure recovery increase. Value of void fraction above 0.2, its became pressure recovery decrease.Keywords: ejector, diffuser, pressure recovery, co-current flow, downward flow, two-phase flow